2005
DOI: 10.1080/00207390500271503
|View full text |Cite
|
Sign up to set email alerts
|

Something strange and useless: service students’ conceptions of statistics, learning statistics and using statistics in their future profession

Abstract: We investigate the views of service students about statistics, learning statistics and using statistics in their future profession, based on information obtained from a series of interviews analysed using a phenomenographic approach. In previous studies, we have described statistics major students' conceptions of their subject and their learning. Our main conclusion is that, contrary to expectations, service students show the same range of variation in their views as do statistics major students. We examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
0
13
0
11
Order By: Relevance
“…The results of our investigations have been published in a series of papers (Petocz & Reid, 2001, 2003, 2005; Reid & Petocz, 2002, 2003). We have also supported this with investigations of teachers' views of teaching statistics and of the characteristics that make “good” students (Gordon et al , 2007).…”
Section: Students' Conceptions Of Statistics Learning and Teachingmentioning
confidence: 99%
“…The results of our investigations have been published in a series of papers (Petocz & Reid, 2001, 2003, 2005; Reid & Petocz, 2002, 2003). We have also supported this with investigations of teachers' views of teaching statistics and of the characteristics that make “good” students (Gordon et al , 2007).…”
Section: Students' Conceptions Of Statistics Learning and Teachingmentioning
confidence: 99%
“…Diante dessa relevância, os cursos universitários da área de ciências aplicadas, como a Administração, Engenharia, Psicologia, Medicina, Turismo etc., costumam possuir disciplinas obrigatórias de Estatística em suas grades curriculares (PAN;TANG, 2004;PETOCZ;REID, 2005). A Estatística é incluída nestes cursos com intuito de capacitar os aprendizes na utilização dos conceitos estatísticos como uma ferramenta de apoio e não como uma habilidade central no contexto profissional, ou seja, a Estatística é considerada um meio e não um fim para estas profissões (PETOCZ; REID, 2005).…”
Section: Ensino De Estatísticaunclassified
“…In other words, because these disciplines use applied statistics, statistics is seen as a service subject in the teaching context. Many students do not know why they have to take a course in statistics or how it is related to their main discipline (Petocz and Reid 2005). One student in an earlier study by Petocz (1998) was reported as saying: ''Statistics is something strange and useless.…”
Section: Introductionmentioning
confidence: 98%